EFEKTIVITAS SARI KEDELAI HITAM (Glycine soja sieb) SEBAGAI BAHAN PANGAN FUNGSIONAL - Nunung Kurniasih; Tina Dewi Rosahdi; Nunik Rahmawati Rahman (JURNAL ISTEK, 2013)
EFFECTIVENESS OF THE BLACK SOYBEAN EXTRACTS AS A FUNCTIONAL FOOD. Black soybean (Glycine soja sieb) has potential as functional food. This is because it have carbohydrates as a source of nutrition (prebiotic) for lactic acid bacteria (probiotic). This research was to determine the effectiveness of the black soybeans extracts as a medium for the growth of lactic acid bacteria, namely Lactobacillus lactis. Sampling is done on fermentation at the 0, 24, 48 and 72 for analysis of total acid, glucose levels and the number of bacteria. Analysis of the levels of lactic acid by qualitative and quantitative methods tertitrasi while total acid, glucose levels by methods Luff Schoorl and the number of bacteria using UV-Vis spectrophotometer. Fermentation extracts black soybeans by Lactobacillus lactis for 72 hours of earned value increased lactic acid levels. Reducing sugar content of both the substrate decreases. The number of bacteria Lactobacillus lactis increased to 72 hours. From the data obtained is known that black soybean extract is effective as a functional food.